T cell suppression in vitro. I. Role in regulation of antibody responses. - Feldmann, M (1974)
Suppression of the antibody response by supraoptimal numbers of T helper cells was studied in vitro and found to have both a specific and a nonspecific component. Suppression did not depend on direct cell contact of T and B cells, as supernatants of activated T cells were just as inhibitory. Suppression by excess T cells (or T cell supernatant) was abrogated by the addition of macrophages. By using a tolerance induction protocol, it was shown that T cell supernatants induce partial tolerance in both T and B cells. This tolerance occurred in three different experimental settings: if adherent cells were physically removed by surface adherence, in the presence of anti macrophage serum, or in the presence of very high concentrations of T cell supernatant. All 3 conditions stress the importance of the interaction between T cell supernatants and macrophages. The nonspecific form of suppression was not analyzed in detail, but was shown to be partly abrogated by macrophages, suggesting that it may be analogous to antigenic competition, one model of which has recently been shown to be abolished by addition of macrophages. The results suggest the presence of homeostatic feedback loops, due to excess T cell function; T cell products suppress the function of T cells, preventing the induction of further helper cells, and also suppress B cells directly. The balance between T cell suppression and cooperation is affected by macrophage function.